Epistemic trust and personality functioning mediate the association between adverse childhood experiences and posttraumatic stress disorder and complex posttraumatic stress disorder in adulthood - Kampling, Hanna; Kruse, Johannes; Lampe, Astrid; Nolte, Tobias; Hettich, Nora; Brähler, Elmar; Sachser, Cedric; Fegert, Jörg M.; Gingelmaier, Stephan; Fonagy, Peter; Krakau, Lina; Zara, Sandra; et al. (Frontiers in Psychiatry, 2022)
Background Adverse childhood experiences (ACEs) are associated with posttraumatic and complex posttraumatic stress disorder symptoms in adulthood (PTSD/cPTSD), as well as reduced epistemic trust (trust in the authenticity and personal relevance of interpersonally transmitted information) and impaired personality functioning. The present work aims to investigate the predictive value of epistemic trust – the capacity for social learning – on the mediating effect of personality functioning in the association of ACEs and PTSD/cPTSD. Methods We conducted structural equation modeling (SEM) based on representative data of the German population (N=2,004). Personality functioning (OPD-SQS) was applied as a mediator between ACEs and PTSD/cPTSD (ITQ), while epistemic trust (ETMCQ) was added as predictor for OPD-SQS. TLI, CFI and RMSEA (95%-CI) determined the models’ fit. Results N=477 (23.8%) participants reported at least one ACE and n=218 (10.9%) reported ≥4 ACEs. Fit indices were good for both PTSD (TLI=.96; CFI=.99; RMSEA=.06; 95%-CI=.041-.078) and cPTSD (TLI = .96; CFI = .99; RMSEA = .06; 95%-CI: .043–.081). ACEs were significantly associated with cPTSD (β=.44, p<.001) and PTSD (β=.29, p<.001), explaining 20% and 8% of its variance. Adding personality functioning as mediator increased the explained variance of cPTSD and PTSD to 47% and 19% while the direct association between ACEs and cPTSD/PTSD decreased (β=.21/β=.17), thus, indicating a partial mediation. Including epistemic trust substantially increased the explained variance for personality functioning (41%) compared to ACEs as a single predictor (16%). Conclusion We add to previous research emphasizing the association between ACEs and PTSD/cPTSD symptoms. Offering insights on underlying mechanisms, we show that epistemic trust and personality functioning are relevant mediators. Since both are modifiable by psychotherapy, knowledge about the role of these constructs can inform research on psychotherapeutic interventions and prevention.